2020
DOI: 10.3390/cells9030536
|View full text |Cite
|
Sign up to set email alerts
|

SHH Signaling Pathway Drives Pediatric Bone Sarcoma Progression

Abstract: Primary bone tumors can be divided into two classes, benign and malignant. Among the latter group, osteosarcoma and Ewing sarcoma are the most prevalent malignant primary bone tumors in children and adolescents. Despite intensive efforts to improve treatments, almost 40% of patients succumb to the disease. Specifically, the clinical outcome for metastatic osteosarcoma or Ewing sarcoma remains poor; less than 30% of patients who present metastases will survive 5 years after initial diagnosis. One common and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 142 publications
(169 reference statements)
0
17
0
Order By: Relevance
“…In several cancers, it has been demonstrated that YAP stimulates cell proliferation largely by controlling the expression of a broad number of cell cycle regulators or the expression of oncogenes, for example MYC and AP-1 family members [ 19 ]. In this work, we identify genes directly involved in the control of cell cycle, such as CDC25B, or involved in the regulation of oncogene expression, such as Gli1 previously described as a pro-proliferation factor and thus as a potential therapeutic target in OS [ 31 ]. Furthermore, using overexpression of a mutant YAP protein unable to interact with TEAD1–4 (YAPS94A), we clearly demonstrate that the TEADs transcriptional factors are crucial in YAP-driven OS growth both in vitro and in vivo as previously described in other cancers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several cancers, it has been demonstrated that YAP stimulates cell proliferation largely by controlling the expression of a broad number of cell cycle regulators or the expression of oncogenes, for example MYC and AP-1 family members [ 19 ]. In this work, we identify genes directly involved in the control of cell cycle, such as CDC25B, or involved in the regulation of oncogene expression, such as Gli1 previously described as a pro-proliferation factor and thus as a potential therapeutic target in OS [ 31 ]. Furthermore, using overexpression of a mutant YAP protein unable to interact with TEAD1–4 (YAPS94A), we clearly demonstrate that the TEADs transcriptional factors are crucial in YAP-driven OS growth both in vitro and in vivo as previously described in other cancers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several cancers, it has been demonstrated that YAP stimulates cell proliferation largely by controlling the expression of a broad number of cell cycle regulators or the expression of oncogenes, for example MYC and AP-1 family members [19]. In this work, we identify genes directly involved in the control of cell cycle, such as CDC25B, or involved in the regulation of oncogene expression, such as Gli1 previously described as a pro-proliferation factor and thus as a potential therapeutic target in OS [30]. Furthermore, using overexpression of a mutant YAP protein unable to interact with TEAD1-4 (YAPS94A), we clearly demonstrate that the TEADs transcriptional factors are crucial in YAP-driven OS growth both in vitro and in vivo as previously described in other cancers [21].…”
Section: Yap/tead Signaling As a Target Therapy Against Primary Tumormentioning
confidence: 91%
“…Aberrant activation of the Sonic Hedgehog (SHH) pathway is another signal transduction pathway that has implications in osteosarcoma development, progression, and metastasis [ 33 ]. A study by Shu et al implicated a role for this pathway in stemness and chemotherapy resistance and observed that by inhibiting heat shock protein 90 (Hsp90) with the small molecule 17-AAG, they suppressed the SHH pathway and reversed chemoresistance [ 34 ].…”
Section: Signal Transductionmentioning
confidence: 99%